Pengaruh Pengetahuan, Tanggung Jawab, dan Inklusi Keuangan terhadap Keberlangsungan Usaha Konveksi - Dyah Putri Azzahroh; Anna Widiastuti (TIN: Terapan Informatika Nusantara, 2026)
Business sustainability is a crucial factor determining the ability of Micro, Small, and Medium Enterprises (MSMEs) to survive and grow amidst uncertain economic dynamics. This study aims to analyze the influence of financial knowledge, financial responsibility, and financial inclusion on the business sustainability of MSMEs in the garment industry in Jepara Regency. The novelty of this research lies in the use of the financial responsibility variable, which has rarely been examined in relation to business sustainability. The study employs a quantitative approach using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. Data were collected via questionnaires distributed to 150 garment business owners selected through probability sampling (specifically, random sampling). The results indicate that financial knowledge has a positive and significant effect on business sustainability, with a path coefficient of 0.465 (t = 4.478; p = 0.000), while financial responsibility also has a positive and significant effect, with a path coefficient of 0.218 (t = 2.444; p = 0.015). Conversely, financial inclusion does not have a significant effect on business sustainability, showing a path coefficient of 0.008 (t = 0.089; p = 0.929). An R-square value of 0.395 indicates that financial knowledge, financial responsibility, and financial inclusion explain 39.5% of the variation in business sustainability, with the remainder influenced by factors outside the research model. These findings confirm that enhancing MSME business sustainability requires more than just expanding access to financial services; it also necessitates strengthening the financial knowledge and financial responsibility of business owners.